Legal Certainty of the Position of Adopted Children in Inheriting the Assets of Their Adoptive Parents According to Samin Customary Law in Blora Regency - Pradana, Charizma Hade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
.